Emergence of a Severe Acute Respiratory Syndrome Coronavirus 2 Virus Variant With Novel Genomic Architecture in Hong Kong. (2nd March 2021) - Tse, Herman; Lung, David Christopher; Wong, Sally Cheuk-Ying; Ip, Ka-Fai; Wu, Tak-Chiu; To, Kelvin Kai-Wang; Kok, Kin-Hang; Yuen, Kwok-Yung; Choi, Garnet Kwan-Yue
Abstract: Throughout the coronavirus disease 2019 (COVID-19) pandemic, divergent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineages have emerged continuously, mostly through the genomic accumulation of substitutions. We report the discovery of a SARS-CoV-2 variant with a novel genomic architecture characterized by absent ORF7a, ORF7b, and ORF8, and a C-terminally modified ORF6 product resulting from partial 5′-untranslated region (UTR) duplication and transposition.